Phagocytic Receptor CED-1 Initiates a Signaling Pathway for Degrading Engulfed Apoptotic Cells - Yu, Xiaomeng (Public Library of Science, 2008)
Apoptotic cells in animals are engulfed by phagocytic cells and subsequently degraded inside phagosomes. To study the mechanisms controlling the degradation of apoptotic cells, we developed time-lapse imaging protocols in developing Caenorhabditis elegans embryos and established the temporal order of multiple events during engulfment and phagosome maturation. These include sequential enrichment on phagocytic membranes of phagocytic receptor cell death abnormal 1 (CED-1), large GTPase dynamin (DYN-1), phosphatidylinositol 3-phosphate (PI(3)P), and the small GTPase RAB-7, as well as the incorporation of endosomes and lysosomes to phagosomes. Two parallel genetic pathways are known to control the engulfment of apoptotic cells in C. elegans. We found that null mutations in each pathway not only delay or block engulfment, but also delay the degradation of engulfed apoptotic cells. One of the pathways, composed of CED-1, the adaptor protein CED-6, and DYN-1, controls the rate of enrichment of PI(3)P and RAB-7 on phagosomal surfaces and the formation of phagolysosomes. We further identified an essential role of RAB-7 in promoting the recruitment and fusion of lysosomes to phagosomes. We propose that RAB-7 functions as a downstream effector of the CED-1 pathway to mediate phagolysosome formation. Our work suggests that phagocytic receptors, which were thought to act specifically in initiating engulfment, also control phagosome maturation through the sequential activation of multiple effectors such as dynamin, PI(3)P, and Rab GTPases.